Jane Austen’s Pride and Prejudice as a Timeless Dramatic Classical Novel - Dr. Ahmed Elhaj Omer Hamed (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
In this paper Jane Austen’s Pride and Prejudice is treated as a timeless dramatic classical novel. It was first published anonymously in three volumes in 1813. Jane Austen seldom describes characters, but instead she uses the art of dramatic presentation. The characters reveal themselves through what they say. The story involved a previous marriage of Mr. and Mrs. Bennet which was based on physical attraction which soon faded. It included the marriage of Elizabeth and Darcy, the marriage of Jane and Bingley, the marriage of Lydia and Wickham and the marriage of Collins and Charlotte Lucas. The relationships and actions related to the characters in the novel are portrayed through the themes of marriage, prejudice, pride, morality, social class and reputation.